PREVALENCE OF ATTENTION-DEFICIENT/HYPERACTIVITY DISORDER CO-MORBIDITIES IN CHILDREN OF SOUTH JORDAN - Ali Nafi, Omar (European Scientific Journal, ESJ, 2013)
The treatment success of attention-deficient/hyperactivity disorder (ADHD) is limited by misdiagnosis or underestimated co-existing conditions, including epilepsy, mental retardation, and autism spectrum disorder. The aim of this study was to document the prevalence of these three ADHD co-morbidities in a single patient population. A total of 107 children (3-12 years) evaluated for ADHD in our neurology clinic (clinical sample) were initially considered for this study. The existence of co-morbidities was determined using parent interview, family history, medical history, developmental history, and neurological evaluation. Results showed that 82 patients (M:F; 60:22) fulfilled the criteria for ADHD diagnosis. The patient population was composed of combined ADHD (51%), hyperactive/impulsive (28%). and inattentive (21%), Boys were about three times more likely to present with combined or hyperactive/impulsive ADHD compared to girls. Among all ADHD children, 70% presented co-morbidity: epilepsy ((29.3%), mental retardation (28%) or autistic spectrum disorder (12.2%). Such common occurrence suggests that the current protocols used to diagnose ADHD should be refined to identify these co-morbidities for the development of a new approach to ADHD. Our findings add relevant clinical information on ADHD from a world region where few clinical studies on this disorder have thus far been conducted.